Epidemiological profile of patients with malignant Brain tumors in Rio Grande do Sul state - Brazil - de Moraes Rêgo Soares, Pedro; Pastorello, Julia; Lando, Emanuela; Rottenfusser, Robson; Mesquita Filho, Paulo Moacir (Brazilian Journal of Case Reports, 2022)
To determine the epidemiological profile of patients diagnosed with primary malignant brain tumors in the state of Rio Grande do Sul/RS, Brazil, from 2013 to 2019. This is a descriptive, retrospective study with a quantitative approach, carried out through analysis of secondary data collected at the Information Technology Department of the Unified Health System (DATASUS). One thousand five hundred and fifty-eight cases of malignant primary brain tumor were diagnosed. The highest prevalence of cases occurred among men (55.78%) and among individuals aged 40 to 59 years (28.34%). The macro-region with the highest incidence was the Metropolitan (45.64%). An expansion of the database is necessary, mainly in some pathological characteristics such as location of the neoplasm, histological type and morbidity and mortality and patient characteristics such as race to better predict risk factors, prevention and diagnosis.